EFFECTIVENESS OF PLAIN SHOULDER RADIOGRAPH IN DETECTING DEGENERATE ROTATOR CUFF TEARS - Hussain, Adnan; Muzzammil, Muhammad; Butt, Faisal; Valsamis, Epaminondas Markos; Dwyer, Amitabh J. (Journal of Ayub Medical College Abbottabad, 2018)
Background: Studies have demonstrated radiographic findings of sclerosis and cortical irregularity at the greater tuberosity can suggest a rotator cuff tear. Plain radiographs are the most easily attainable first-line investigations in evaluating shoulder injuries. This study determines the effectiveness in predicting degenerate rotator cuff tears by detecting radiographic changes on shoulder x-rays. Methods: Retrospective cross-sectional study with a consecutive series of patients conducted in Hinchingbrooke Hospital, Huntingdon, United Kingdom from January 2015 to June 2017. Anteroposterior shoulder radiographs of 150 symptomatic patients who underwent shoulder arthroscopy were independently analysed by surgeons who were blinded from the arthroscopic results. Patients aged under 30 and over 70 years were excluded. Patients with advanced osteoarthritis and cuff tear arthropathy evident on x-rays were also excluded. Sixty-five patients included in the study had rotator cuff tears on arthroscopy. Radiographic changes were correlated with arthroscopic findings to determine this test’s ability to predict degenerate rotator cuff tears. Results: When both cortical irregularity and sclerosis were present on the plain radiograph, these signs had a sensitivity of 78.8% [95% CI 65.7, 87.8%] and specificity 77.4% [95% CI 67.2, 85.0%] with a positive predictive value of 68.3%, using contingency table analysis. The presence of cortical irregularity was found to be a better predictor of a tear as compared to sclerosis. Conclusions: This study concludes that plain radiograph are good modality for initial evaluation of rotator cuff tears and detecting when both cortical irregularity and sclerosis. Consideration of these radiographic findings serves as a useful adjunct in diagnostic workup and can guide subsequent investigations and treatment when evaluating rotator cuff tears of the shoulder Keywords: Effectiveness; Plain Radiograph; Shoulder; Degenerate; Rotator Cuff Tears